2019
DOI: 10.1097/fbp.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Validation of chronic mild stress in the Wistar-Kyoto rat as an animal model of treatment-resistant depression

Abstract: A recent review proposed four criteria for an animal model of treatment-resistant depression (TRD): a phenotypic resemblance to a risk factor for depression; enhanced response to stress; nonresponse to antidepressant drugs and response to treatments effective in TRD, such as deep brain stimulation (DBS) of the prefrontal cortex or ketamine. Chronic mild stress (CMS) provides a valid model of depression; the Wistar-Kyoto (WKY) rat is considered to be nonresponsive to antidepressant drugs. Here, we applied CMS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 71 publications
6
52
0
Order By: Relevance
“…fear conditioning tests) 49 . On note, in the literature addressing the performance of Kyoto rats in the EPM, Langen and Dost 50 , and Willner 51 reported an anxious profile for this strain, however other authors 15,16 showed no differences when comparing it with the Wistar rat. Taken together, these results suggest that the behavioural parameters measured in the EPM are not consistent when applied to characterize a rodent strain (trait), which is supposed to be stable over time, at least without treatment 52 .…”
Section: Discussionmentioning
confidence: 91%
“…fear conditioning tests) 49 . On note, in the literature addressing the performance of Kyoto rats in the EPM, Langen and Dost 50 , and Willner 51 reported an anxious profile for this strain, however other authors 15,16 showed no differences when comparing it with the Wistar rat. Taken together, these results suggest that the behavioural parameters measured in the EPM are not consistent when applied to characterize a rodent strain (trait), which is supposed to be stable over time, at least without treatment 52 .…”
Section: Discussionmentioning
confidence: 91%
“…Certainly, perseveration has been proved to be augmented by stress 67 . It has been repeatedly observed that CUS decreases the discrimination index either marginally 68 or significantly 6974 , although others have reported that only a subset of CUS responders shows memory impairments in the ORT 75 . The lack of significant differences in the discrimination index may be related to the features of the objects used.…”
Section: Resultsmentioning
confidence: 99%
“…CUS-exposed rodents that fail to respond to conventional antidepressants are considered non-responders 84 , 85 . Also, Wistar-Kyoto rats subjected to CUS have been recently validated as a model of TRD 86 , 87 . Notably, these models showed a good response to deep brain stimulation 84 87 ; however, the effects of rTMS in these treatment-resistant animals have not yet been studied.…”
Section: Discussionmentioning
confidence: 99%